2016
DOI: 10.1186/s12941-016-0145-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SLOMYCO Sensititre® panel for testing the antimicrobial susceptibility of Mycobacterium marinum isolates

Abstract: BackgroundThe agar dilution method is currently considered as the reference method for Mycobacterium marinum drug susceptibility testing (DST). As it is time-consuming, alternative methods, such as the E-test, were evaluated for M.marinum DST, but without success. The SLOMYCO Sensititre® panel, recently commercialized by TREK Diagnostic Systems (Cleveland, OH), can be used for DST in slow-growing mycobacteria and for antimicrobial agents recommended by the Clinical and Laboratory Standards Institute (CLSI) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Mycobacterium marinum is a slow-growing nontuberculous photochromogenic mycobacteria. It is a ubiquitous waterborne organism, inhabiting fresh and saltwater and causes disease in many fish species and occasionally in humans ( 1 , 2 ). It is also known to cause a false positive reaction to interferon-γ (IFN-γ) release assay (IGRA) for the diagnosis of latent tuberculosis infection (LTBI) ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterium marinum is a slow-growing nontuberculous photochromogenic mycobacteria. It is a ubiquitous waterborne organism, inhabiting fresh and saltwater and causes disease in many fish species and occasionally in humans ( 1 , 2 ). It is also known to cause a false positive reaction to interferon-γ (IFN-γ) release assay (IGRA) for the diagnosis of latent tuberculosis infection (LTBI) ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, M. marinum has been proven to be a useful model for the identification of potential antimycobacterial compounds (7)(8)(9)(10). However, M. marinum and M. tuberculosis possess distinct susceptibility levels to a number of antimycobacterial drugs, notably, ethionamide (ETH) and isoniazid (INH) (7,11,12). These observations indicate that there are significant differences between M. tuberculosis and M. marinum, which may hinder the efficacy of antimycobacterial drug discovery when using M. marinum as a screening model.…”
mentioning
confidence: 99%
“…The converted metabolites form adducts with NAD 1 and subsequently bind to inhibit InhA, which is essential for mycolic acid synthesis (16). In several studies, the MICs of ETH and INH were observed to be among the most contrasting between M. tuberculosis and M. marinum (11,12). For the activation of INH, this could be attributed to small differences between the KatG structures of M. marinum and M. tuberculosis (17).…”
mentioning
confidence: 99%